Genetic characterization of ESBL-producing and ciprofloxacin-resistant Escherichia coli from Belgian broilers and pigs - De Koster, Sien; Ringenier, Moniek; Xavier, Basil Britto; Lammens, Christine; De Coninck, Dieter; De Bruyne, Katrien; Mensaert, Klaas; Kluytmans-van den Bergh, Marjolein; Kluytmans, Jan; Dewulf, Jeroen; Goossens, Herman; , on behalf of the i-4-1-Health Study Group (Frontiers in Microbiology, 2023)
The increasing number of infections caused by Escherichia coli resistant to clinically important antibiotics is a global concern for human and animal health. High overall levels of extended-spectrum beta-lactamase (ESBL)-producing and ciprofloxacin-resistant (ciproR) E. coli in livestock are reported in Belgium. This cross-sectional study aimed to genotypically characterize and trace ESBL-and ciproR-E. coli of Belgian food-producing animals. A total of 798 fecal samples were collected in a stratified-random sampling design from Belgian broilers and sows. Consequently, 77 ESBL-E. coli and 84 ciproR-E. coli were sequenced using Illumina MiSeq. Minimum inhibitory concentration (MIC) for fluoroquinolones and cephalosporins were determined. Molecular in silico typing, resistance and virulence gene determination, and plasmid identification was performed. Scaffolds harboring ESBL or plasmid-mediated quinolone resistance (PMQR) genes were analyzed to detect mobile genetic elements (MGEs) and plasmid origins. Core genome allelic distances were used to determine genetic relationships among isolates. A variety of E. coli sequence types (ST)(n=63), resistance genes and virulence profiles was detected. ST10 was the most frequently encountered ST (8.1%,n=13). The pandemic multidrug-resistant clone ST131 was not detected. Most farms harbored more than one ESBL type, with blaCTX-M-1 (41.6% of ESBL-E. coli) being the most prevalent and blaCTX M-15 (n=3) being the least prevalent. PMQR genes (15.5%,n=13) played a limited role in the occurrence of ciproR-E. coli. More importantly, sequential acquisition of mutations in quinolone resistance-determining regions (QRDR) of gyrA and parC led to increasing MICs for fluoroquinolones. GyrA S83L,D87N and ParC S80I mutations were strongly associated with high-level fluoroquinolone resistance. Genetically related isolates identified within the farms or among different farms highlight transmission of resistant E. coli or the presence of a common reservoir. IncI1-I(alpha) replicon type plasmids carried different ESBL genes (blaCTX-M-1,blaCTX-M-32 and blaTEM-52C). In addition, the detection of plasmid replicons with associated insertion sequence (IS) elements and ESBL/PMQR genes in different farms and among several STs (e.g. IncI1-I(alpha)/IncX3) underline that plasmid transmission could be another important contributor to transmission of resistance in these farms. Our findings reveal a multifaceted narrative of transmission pathways. These findings could be relevant in understanding and battling the problem of antibiotic resistance in farms.